2016
DOI: 10.1073/pnas.1522008113
|View full text |Cite
|
Sign up to set email alerts
|

Inbreeding drives maize centromere evolution

Abstract: Functional centromeres, the chromosomal sites of spindle attachment during cell division, are marked epigenetically by the centromerespecific histone H3 variant cenH3 and typically contain long stretches of centromere-specific tandem DNA repeats (∼1.8 Mb in maize). In 23 inbreds of domesticated maize chosen to represent the genetic diversity of maize germplasm, partial or nearly complete loss of the tandem DNA repeat CentC precedes 57 independent cenH3 relocation events that result in neocentromere formation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
98
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(107 citation statements)
references
References 46 publications
9
98
0
Order By: Relevance
“…Although this result may not be so surprising in the case of a close relative such as L. oleraceum CENH3, it is remarkable for Z. mays CENH3. The association between CENH3 nucleosomes and maize DNA is variable, as multiple relocation events have been characterized in the domesticated population (Schneider et al 2016). There is no sequence similarity between centromeric sequences of the monocot Z. mays and dicot A. thaliana.…”
Section: Discussionmentioning
confidence: 99%
“…Although this result may not be so surprising in the case of a close relative such as L. oleraceum CENH3, it is remarkable for Z. mays CENH3. The association between CENH3 nucleosomes and maize DNA is variable, as multiple relocation events have been characterized in the domesticated population (Schneider et al 2016). There is no sequence similarity between centromeric sequences of the monocot Z. mays and dicot A. thaliana.…”
Section: Discussionmentioning
confidence: 99%
“…Alignment of chromatin immunoprecipitation followed by sequencing (ChIP-seq) data for the centromere specific histone H3 (CENH3) 14 revealed that centromeres are accurately placed and largely intact. Several previously identified 15 megabase sized mis oriented pericentromeric regions were also corrected (Extended Data Fig. 3a, b).…”
Section: Openmentioning
confidence: 99%
“…7). The high density of alignments across and near many of the exceedingly retrotransposon rich centromeres reflects the comparatively low genetic diversity of most centromeres in domesticated maize 15 and illustrates the ability of the combined optical mapping/single molecule sequencing methodology to traverse large repeat rich regions. Within the aligned regions, approximately 32% of the Ki11 and 26% of the W22 optical maps exhibited clear evidence of structural variation, including 3,408 insertions and 3,298 deletions ( Table 2).…”
Section: Openmentioning
confidence: 99%
“…The domestication of selfish elements appears to be responsible for the most remarkable example of centromere evolution, the partial or complete replacement of the satellite centromeres of the wild ancestor of maize by a selfish element in maize inbred lines (Schneider et al 2016). During domestication of maize from teosinte over the past ∼9000 years, selection for agronomic traits was accompanied by dense insertion of CR2 centromerespecific retrotransposons and frequent loss by small inversions and deletions of the ancestral 155-bp CentC satellite in all 10 maize centromeres, 57 times independently in 26 inbred lines.…”
Section: Understanding the Evolutionary Plasticity Of Centromeric Chrmentioning
confidence: 99%